2017
DOI: 10.1021/jacs.6b13261
|View full text |Cite
|
Sign up to set email alerts
|

Dicopper Cu(I)Cu(I) and Cu(I)Cu(II) Complexes in Copper-Catalyzed Azide–Alkyne Cycloaddition

Abstract: A discrete, dicopper μ-alkynyl complex, [Cu(μ-η:η-C≡C(CH)CH)DPFN]NTf (DPFN = 2,7-bis(fluoro-di(2-pyridyl)methyl)-1,8-naphthyridine; NTf = N(SOCF)), reacts with p-tolylazide to yield a dicopper complex with a symmetrically bridging 1,2,3-triazolide, [Cu(μ-η:η-(1,4-bis(4-tolyl)-1,2,3-triazolide))DPFN]NTf. This transformation exhibits bimolecular reaction kinetics and represents a key step in a proposed, bimetallic mechanism for copper-catalyzed azide-alkyne cycloaddition (CuAAC). The μ-alkynyl and μ-triazolide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 82 publications
(162 reference statements)
5
110
0
1
Order By: Relevance
“…The most accepted mechanism of Huisgen 1,3-Dipolar cycloaddition ("Click Reaction") involved the two copper centered transition state. [16][17][18][19][20][21] The reaction initiated with the activation of alkyne with the aid of two copper atoms which facilitated the attack of negative centered nitrogen of sugar azide over the alkyne and trough the concerted cycloaddition the desired products were formed ( Figure 2).…”
Section: Chemistrymentioning
confidence: 99%
“…The most accepted mechanism of Huisgen 1,3-Dipolar cycloaddition ("Click Reaction") involved the two copper centered transition state. [16][17][18][19][20][21] The reaction initiated with the activation of alkyne with the aid of two copper atoms which facilitated the attack of negative centered nitrogen of sugar azide over the alkyne and trough the concerted cycloaddition the desired products were formed ( Figure 2).…”
Section: Chemistrymentioning
confidence: 99%
“…Indeed, quite a number of 2 and/or 7-substituted 1,8-naphthyridine-based ligands have been investigated for their coordination and catalytic activity. [2][3][4][5][6][7][8][9][10] Besides acting as a donor in coordination, the nitrogen atom in naphthyridine is also able to act as a pendant group to serve as a base for promotion of the catalytic reactions. In a recent report, Bera et al found that complex [RuH(CO)(py-NP)(PPh3)2]Cl [py-NP = 2-pyridinyl-1,8-naphthyridine] is able to catalyze the oxidation of primary alcohols into the corresponding carboxylic acid via the dehydrogenation of alcohol followed by a hydroxide/water attack on the metalbound aldehyde.…”
Section: Introductionmentioning
confidence: 99%
“…Many examples The Cu(I)-dppm complexes are emerging class of polynuclear complexes, that are drawing considerable attention because of their photophysical properties [19][20][21][22] and prospective use as a catalyst [23][24][25] and a sensor for various organic bases [26] and anions [27]. Binuclear Cu(I) species possess an enhanced reactivity toward organic azides in copper-catalysed azide-alkyne cycloaddition compared to monomeric copper complexes [28][29][30][31][32][33][34][35]. Copper(I) tetrahydroborates with phosphine ligands featuring relative stability to air oxygen and moisture are used as selective reducing agents [36][37][38][39][40], catalysts of photosensitized isomerization of dienes [41][42][43] and hydrolytic dehydrogenation of ammonia borane [44].…”
Section: Introductionmentioning
confidence: 99%
“…Binuclear Cu(I) species possess an enhanced reactivity toward organic azides in copper-catalysed azide-alkyne cycloaddition compared to monomeric copper complexes [28][29][30][31][32][33][34][35]. Copper(I) tetrahydroborates with phosphine ligands featuring relative stability to air oxygen and moisture are used as selective reducing agents [36][37][38][39][40], catalysts of photosensitized isomerization of dienes [41][42][43] and hydrolytic dehydrogenation of ammonia borane [44].…”
Section: Introductionmentioning
confidence: 99%